Controversies regarding the Covid-19 pandemic in national and international tourism. Sociological and legal effects - Oprescu Georgiana (Technium Social Sciences Journal, 2020)
The approaches considered by the authorities, generally enforced, during the “Covid 19” pandemic regarding the state of national and international tourism have been characterised as excessive and controversial not only from an economical point of view but as well as from a cultural and functional one, and they must be analysed from a sociological perspective. The shortage of medical, organisational and human resources, the lack of mental preparation of medical workers but as well as that of the population in terms of preventing massive losses led to the rapid destruction of what we used to call tourism. From a sociological perspective the world-wide blockage was mainly caused by the superficiality of the prevention methods adopted and by their radicality that blocked the entire economy. By this article I try to approach from a from a sociological point of view the “pandemic” effects that that have influenced and are still influencing tourism. In extenso, the plethora of factors like public transportation, hospitals, workplace and so on have provoked the rapid spread of COVID-19 virus and the impact was ravaging for the hospitality industry due to the fact that the client in his role of tourist received only negative signal, signals of fear and uncertainty. The controversies regarding different fields of national and international tourism are various in number, but the present interest lies in COVID-19 virus and a consequence of this plague is the foreclosure as opposed to the fact that by imposing the right measurements and by protecting this field in a composed way without letting panic to reach the population it would have been possible to at least mentain a constant level of activity in tourism and as a consequence a steady national and international economy. Furthermore, I want to issue the assumption that if there would have been a propper crisis-management on a national level, even on international one, a partnership between the government and the private sector, meaningfull aid coming from government towards the people, employees, antreprenours, elders, lower-class families, private inverstors, not only that from an economical point of view tourism could be saved but also a “positive aura” could have been built in the psyche of the individuals and that would have helped them to have a diffrent type of confinment. For excample, a 10 days stay in a highly reviewed an alternative method - provocative, peacefull and safe- but to acomplish this the hoteliere should revise the concept on which a touritic package is built (by offering services as therapy, medical check-up and so on). The motto of the new concept could be the old saying “A healthy mind in a healthy body“ -”Mens sana in corpore sano” in this way the panic, fear and seclusion could be replaced with cultural work and the right to mental wellness with the help ground-braking touristic offers. From a sociological perspective, in order to have a healthy mind in a healthy body or in order to strengthen our immune system, we, the ones that form the contemporary society should exploit outdoor activities, relaxation time, travelling, living, all this leading to the reinforcement of tourism